HUBUNGAN INTENSITAS PENGGUNAAN GAWAI DENGAN KUALITAS TIDUR PADA REMAJA DI SMP N 1 NGAWEN - INDAH LESTARI, DEVI NAFIROH; Yeni Rusyani; Feri Catur Yuliani (CV. ALIM'SPUBLISHING, 2024)
Background: According to APJII (Association of Indonesian Internet Providers) found that the number of Internet users in Indonesia is 143.26 million people or around 54.68% of the total Indonesian population of 256.2 million people (Risna, 2021). Objective: This study aims to determine the relationship between the intensity of device use and sleep quality in adolescents at SMP N 1 Ngawen. Research Methods: This research is a quantitative correlational type with a cross sectional approach. The population of this study were all students of SMP N 1 Ngawen totaling 762 students. The sampling technique used puposive sampling. The instruments used were the Use of Gadgets questionnaire and the PSQI (Pittsburg Sleep Quality Index) Questionnaire. Data were analyzed using Spearman Rank. Results: The characteristics of respondents in this study were the majority of 14 years old (41.0%), female gender (48.0%), male gender (52.0%), the majority of high device usage (87%), and the majority of poor sleep quality (96%). Spearman rank obtained a value of 0.000 (p < 0.0005). Conclusion: There is a relationship between the intensity of gadget use and sleep quality in adolescents at SMP N 1 Ngawen.